Test of the gravitational redshift with stable clocks in eccentric orbits: application to Galileo satellites 5 and 6. (11th November 2015) - Delva, P; Hees, A; Bertone, S; Richard, E; Wolf, P
Abstract: The Einstein Equivalence Principle (EEP) is one of the foundations of the theory of General Relativity and several alternative theories of gravitation predict violations of the EEP. Experimental constraints on this fundamental principle of nature are therefore of paramount importance. The EEP can be split into three sub-principles: the universality of free fall (UFF), the local Lorentz invariance (LLI) and the local position invariance (LPI). In this paper we propose to use stable clocks in eccentric orbits to perform a test of the gravitational redshift, a consequence of the LPI. The best test to date was performed with the Gravity Probe A (GP-A) experiment in 1976 with an uncertainty of Our proposal considers the opportunity of using Galileo satellites 5 and 6 to improve on the GP-A test uncertainty. We show that considering realistic noise and systematic effects, and thanks to a highly eccentric orbit, it is possible to improve on the GP-A limit to an uncertainty around after one year of integration of Galileo 5 and 6 data.